Improving Reading Comprehension in English for Nusantara: A Case Study - Syahid, Abdul; Anggraini, Aprillia; Hafizah, Azizatun; Ikrimah, Ikrimah; Nadia, Nadia (Indonesian Journal Publisher, 2024)
This research investigates the effectiveness of using the textbook